Lemon Bacopa: Bacopa caroliniana - Lyn A. Gettys; Carl J. Della Torre (EDIS)
Lemon bacopa is a native aquatic and wetland plant that is a welcome inclusion in a variety of settings, including water gardens, aquatic ponds, and wetland restoration and mitigation sites. The species is broadly adapted and extremely common throughout Florida, and its perennial nature assures a stellar performance year after year. Although lemon bacopa can be weedy in some situations, it is most often considered a beneficial native plant that brings a number of desirable characteristics to almost any aquatic setting. This 3-page fact sheet was written by Lyn Gettys and Carl J. Della Torre III, and published by the UF Department of Agronomy, April 2015. (Photo: Lyn Gettys, UF/IFAS)